Blockchain and Cryptocurrency: The World of Blockchain and Cryptocurrency - Shekar, Greeshma C (International Journal of Computer Sciences and Engineering, 2021)
The primary aim of Blockchain Technology is to maintain a wide variety of digital information that can be efficiently documented and distributed but, makes it difficult or impossible to edit, hack or cheat the system. In other words, the Blockchain Technology ensures security, transparency as well as decentralization of the digital asset. It can also be thought as a chain or interconnected records, that is stored in the form of blocks which is controlled by no single authority. Blockchain Technology forms the substratum for Bitcoin and other Cryptocurrencies. The Cryptocurrencies can operate without the need for central authority, with the help of Blockchain Technology. This research paper deals with how the World of Cryptocurrency is driven by the Blockchain Technology.